Double Negation Sentence to Prioritize Object on R12 in Economic Covid Era - Aziz, R. Mochamad (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
The purpose of this study is to analyze double negation words with no and except to prioritize object on R12 approach in an economic covid era that conjunction to Holy Book. In Quran 51.56 that has worship first then human according to the constant 12 and the formula of hahslm 472319 in the economic age of covid. These research objects are the holy book and formulas of R-12 and R-47. Research is studied through a search of books, journals, holy books, and other electronic media. The methodology used is analytical descriptive in analogies and negatory sentences in Indonesian grammar. The method employed is the similarity and reflexivity of the hahslm 472319. The result is the analogy of R-12 as worship before the universe in the form of paying for food versus eating-paying can be compared with the sentence in QS. Adz-Dzariyat [51]:56. The conclusion is that the subject, I, in the negation sentence, did not create humans first then humans order to worship. But I, first made the design of worship, then continue with creating humans. These God words are the same with blueprint of course semester content. This RPS also can adapt with economic covid age.